Pengawasan Pemerintah Daerah terhadap Limbah Usaha Batik di Kota Jambi - Mhd Ansori; Nuraini Nuraini (Universitas Batanghari Jambi, 2020)
Large, medium, and small industries have been developed in Jambi City. One of these is a batik – textile with unique traditional pattern – industry. The batik industry is not spared from the supervision of the Jambi City Environment Office, especially related to batik waste. Regional governments in carrying out their duties are assisted by agencies, then regional regulations are formed to carry out regional government. The Government of the City of Jambi through the Office of the Environment of the City of Jambi as the Office responsible for environmental management, has made various efforts to manage and control the environment which is carried out annually directly or indirectly. Schematically, supervision is divided into two types, namely firstly administrative supervision in the form of inherent supervision and functional supervision, and secondly oversight by judicial authority, both civil and administrative. This paper aims to determine and analyze local government supervision of batik waste in the city of Jambi. This1type of1research used1is normative1juridical1research, this1research1uses